Analisis Pengaruh Nilai Tukar, Tingkat Suku Bunga, dan Produk Domestik Bruto Terhadap Foreign Direct Investment Di Indonesia - Mayiya Putri Evinda; Moehadi Moehadi; Retno Muslinawati (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2025)
The main focus of this study is to analyze the influence of exchange rates, interest rates, and Gross Domestic Product (GDP) on Foreign Direct Investment (FDI) in Indonesia during the period 2004-2024. The method used is multiple linear regression analysis with quantitative data obtained from official sources and economic databases. The results of this study indicate that simultaneously, all three variables have a significant effect on FDI in Indonesia. Partially, interest rates have a positive and significant effect on FDI, while exchange rates and GDP do not show a significant relationship or influence. This finding indicates that monetary policy that maintains interest rate stability can increase the attractiveness of foreign investment. In addition, other factors such as political stability and security also play an important role in attracting FDI. This study provides policy implications for increasing Indonesia's economic competitiveness and supporting sustainable growth by strengthening these important factors.